Vibration transmission and support loss in MEMS sensors - Chouvion, Benjamin (2010)
Micro-Electro-Mechanical Systems (MEMS) inertial sensors that are based on a resonating structure are used in a wide range of applications including inertial guidance and automotive safety systems. Damping has a significant and negative effect on sensor performance and there is an increasing need to accurately predict and control damping levels, particularly for high performance guidance and navigation applications. Support loss, which governs the losses from the resonator to its foundation through the supporting structure, is an important source of damping in MEMS resonators. This thesis focuses on improving the understanding of this particular damping mechanism and on developing efficient models to predict support loss at the design stage.